Effect of Injection Vitamin B-Complex on Diet for Consumption, Feed Rate Conversion and Average Daily Weight Gain of Bali Cattle in the Growing Phase - Carlito de Araújo Mali Code; Graciano Soares Gomes; Armando B.M. Afonso; Ana Maria da Costa G. Noronha (JURNAL TRITON, 2023)
The use of Vitamin B-complex injection is considered more practical, low cost, and easier in the implementation process, and the role of Vitamin B-complex is as a cofactor in the metabolic process and stimulates voluntary consumption. The aim of this study is to find out the effect of injecting different cc (ml) of B-Complex vitamins on diet intake, feed conversion, and average daily weight gain of Bali cattle in the growing phase. This study was carried out in the municipality of Bobonaro, with a duration of 81 days. The experimental method was used with T-test statistics. The independent groups represent two groups of male cattle and each group is composed of 5 male cattle. The groups are called A, and B, therefore, group A receives an injection of Vitamin B-Complex according to the initial weight of each animal, and group B as a control without Vitamin-B-Complex injection. Both groups received the same diet which is composed of Leucaena leucocephala, Gliricydia spium, Panicum maximum, and rice straw (Oryza sativa Lin). The results of the statistical analysis revealed that there was no difference (P>0.05) between the two groups, mainly in dry matter intake, feed conversion, and average daily weight gain. Therefore, the injection of Vitamin B-Complex should be less necessary to promote the growth of ruminant animals, mainly cattle, due to the degradation of the vitamins in the rumen, in addition to the fact that the vitamin acts by competitive inhibition at different points in the metabolism process, in addition to its participation, it is also fundamental in the oxidation of substrates and energy supply in the animal's metabolism process.